Exploring the context in which different close-to-community sexual and reproductive health service providers operate in Bangladesh: a qualitative study - Mahmud, Ilias; Chowdhury, Sadia; Ashraf Siddiqi, Bulbul; Theobald, Sally; Ormel, Hermen; Biswas, Salauddin; Tauseef Jahangir, Yamin; Sarker, Malabika; Faiz Rashid, Sabina (© 2015 BioMed Central Ltd., 2016)
This article was published in Human Resources for Health [© 2015 BioMed Central Ltd.] and the definite version is available at: https://human-resources-health.biomedcentral.com/articles/10.1186/s12960-015-0045-z